Use of the Goldberg General Health Questionnaire (QSG-12) to assess the impacts of the COVID-19 pandemic on the psyche of members of the academic community at a private university in the south of the country (Research, Society and Development, 2024)
Objective: to evaluate the impacts of COVID-19 on the mental health of the academic community of a private higher education institution located in the Northwest of the state of Rio Grande do Sul, through the General Health Questionnaire (QSG-12). Methodology: this is an observational, cross-sectional, analytical, quantitative, population-based study, carried out at a University in the northwest of the state of Rio Grande do Sul, located in the city of Santo ngelo. Data collection was carried out using a research instrument composed of questions related to the sociodemographic profile, in addition to the application of QSG 12 to evaluate the psyche of the participating individuals. Information was collected using Google Forms. Results: 568 people participated in the research, most of them students, of whom a considerable proportion declared having felt at least one physical discomfort during isolation, with a predominance of tiredness, insomnia, pain and anxiety. In the QSG-12, more than half of the participants reported difficulties with attention, sleep and anxiety control, a fact that highlights the impacts of the Pandemic on the psyche of these individuals. Furthermore, there has been a considerable increase in the use of psychotropic medications as a response to these impasses. Conclusion: The study showed that the university community presented negative aspects such as the impacts of isolation resulting from COVID-19, which mainly affected the mental health of individuals. It is suggested that new studies be carried out, given that this research has limitations as it is located within a single environment.